The influence of environmental factors in motor and social performance of children from the suburb of Porto Alegre - Zajonz, Ricieli; Müller, Alessandra Bombarda; Valentini, Nadia Cristina (Journal of Physical Education (Maringá), 2008)
The objective of this study was to identify children with social and motor delay; verify if delays were associated with ambient factors of risk; and, to verify the impact of motor skill intervention in the motor and social development of children in social vulnerability. The participants (43 children between 06 and 18 months of age) were assessed using the EDCC and AIMS scales. The results showed that: (1) 19 children presented development levels below that what is expected for their age; (2) social development was higher in families that the father was present and had greater social-economics status; (3) motor development was superior in children who mothers had more time to breastfeeding and greater socio economic status. Group comparisons showed that daycare intervention was more effective than domiciliary intervention in terms of providing changes in motor and social development of children at risk.